Electro-Encephalography and Electro-Oculography in Aeronautics: A Review Over the Last Decade (2010–2020) - Belkhiria, Chama; Peysakhovich, Vsevolod (Frontiers in Neuroergonomics, 2020)
Electro-encephalography (EEG) and electro-oculography (EOG) are electrophysiological monitoring methods, particularly fruitful for neuroscience investigation, clinical exploration, aeronautical, and human factors applications. These methods are the most straightforward to evaluate brain oscillations and eye movements using standard laboratory or mobile techniques. EEG and EOG signals can be used to design brain-computer interfaces (BCI) and to interpret brain activity such as pilots’ mental state and workload. This review describes the potential that is carried by such systems, especially in terms of aeronautics applications. The main objectives are: i) To offer an in-depth review literature of basics of EEG and EOG and their application in aeronautics; ii) To explore the methodology and trends of last decade research in combined EEG-EOG studies; iii) To provide methodological guidelines for beginners and experts to investigate out-laboratory environments including human factors and aeronautics. We referred to the main databases that have crossed science, clinical, and neural engineering fields. First, we introduced the characteristics and the aeronautics application of both EEG and EOG from a large panel of literature widening from the oldest to the most recent relevant studies. Then, we built a novel taxonomy model including 150 combined EEG-EOG papers that were published in peer-reviewed scientific journals and conferences in a period between January 2010 and March 2020. For each study, several data elements were reviewed (e.g. extracted features, pre-processing, and performance metrics). We finely examined these components to uncover the trends in aeronautics and summarize interesting methods from this important body of literature. Finally, we examined the advantages and limitations of these methods as well as future challenges.